Inkjet Printed Planar Coil Antenna Analysis for NFC Technology Applications. (22nd March 2012) - Ortego, I.; Sanchez, N.; Garcia, J.; Casado, F.; Valderas, D.; Sancho, J. I.
Abstract : The aim of this paper is to examine the potential of inkjet printing technology for the fabrication of Near Field Communication (NFC) coil antennas. As inkjet printing technology enables deposition of a different number of layers, an accurate adjustment of the printed conductive tracks thickness is possible. As a consequence, input resistance and Q factor can be finely tuned as long as skin depth is not surpassed while keeping the same inductance levels. This allows the removal of the typical damping resistance present in current NFC inductors. A general methodology including design, simulation, fabrication, and measurement is presented for rectangular, planar-spiral inductors working at 13.56 MHz. Analytical formulas, computed numerical models, and measured results for antenna input impedance are compared. Reflection coefficient is designated as a figure of merit to analyze the correlation among them, which is found to be below −10 dB. The obtained results demonstrate the suitability of this technology in the fabrication of low cost, environmentally friendly NFC coils on flexible substrates.